Application of alternative filler in asphalt mixture : An overview from Indonesia perspective - Maha, M. R.A.; Khairul Idham, M.; Mohd Rosli, Hainin; Siti Nur Naqibah, Kamarudin; Amirah, N. A. (IOP Publishing Ltd, 2022)
A good quality and proper quantity of filler material is one of the significant factors in producing asphalt mixture. Many studies have been highlighted waste material as an alternative filler to improve asphalt mixture performance. Hence, this paper reviewed the performance of asphalt mixture using rice husk ash (RHA) as filler in terms of the Marshall properties. It shows that 6% RHA by weight of total aggregate was commonly used and depicted better in Marshall properties than the others. This study also found that the RHA can be used to replace up to 100% of the conventional filler. Even though, higher RHA content could significantly reduce the stability yet it still within the acceptable range and could be applied at medium traffic load road. In return, the higher the RHA content the more waste material can be utilized for road construction. Thus, minimized the usage natural source materials.